KCNK18 biallelic variants associated with intellectual disability and neurodevelopmental disorders alter TRESK channel activity - Pavinato, L; Nematian-Ardestani, E; Zonta, A; De Rubeis, S; Buxbaum, J; Mancini, C; Bruselles, A; Tartaglia, M; Pessia, M; Tucker, SJ; D'Adamo, MC; Brusco, A (MDPI, 2021)
The TWIK-related spinal cord potassium channel (TRESK) is encoded by KCNK18, and variants in this gene have previously been associated with susceptibility to familial migraine with aura (MIM #613656). A single amino acid substitution in the same protein, p.Trp101Arg, has also been associated with intellectual disability (ID), opening the possibility that variants in this gene might be involved in different disorders. Here, we report the identification of KCNK18 biallelic missense variants (p.Tyr163Asp and p.Ser252Leu) in a family characterized by three siblings affected by mild-to-moderate ID, autism spectrum disorder (ASD) and other neurodevelopment-related features. Functional characterization of the variants alone or in combination showed impaired channel activity. Interestingly, Ser252 is an important regulatory site of TRESK, suggesting that alteration of this residue could lead to additive downstream effects. The functional relevance of these mutations and the observed co-segregation in all the affected members of the family expand the clinical variability associated with altered TRESK function and provide further insight into the relationship between altered function of this ion channel and human disease.